2022
DOI: 10.3390/ani12091212
|View full text |Cite
|
Sign up to set email alerts
|

Use of Gnawing Hay Blocks: Effects on Productive Performance, Behavior and Reactivity of Growing Rabbits Kept in Parks with Different Sex-Group Compositions

Abstract: To improve animal welfare in collective park housing systems, this study assessed the effects of the provision of gnawing hay blocks and the group composition (F: females, M: males, FM: mixed sex) on performance, behavior, and reactivity of 288 growing rabbits reared in 18 parks (16 rabbits/park) from 31 to 73 days of age. The presence of gnawing blocks inside the feeding area of the parks scarcely affected performance and budget time, but decreased the time spent in the resting area compared to parks without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Previous studies have also shown positive effects of consumable cage enrichment, such as the introduction of gnawing blocks, which reduced nest box inspections by does and decreased nervousness in fattening rabbits (34,35). In the study of Birolo et al (36), growing rabbits housed in groups exhibited active and Rabbit activity scores (as a proxy for social unrest) averaged per multi-litter cage (N = 15 per treatment) treatment and observation day (1, 3, 6, 8, and 10 days after grouping). Higher activity scores represent a higher amount of movement and thus a higher rate of social unrest in the cage.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies have also shown positive effects of consumable cage enrichment, such as the introduction of gnawing blocks, which reduced nest box inspections by does and decreased nervousness in fattening rabbits (34,35). In the study of Birolo et al (36), growing rabbits housed in groups exhibited active and Rabbit activity scores (as a proxy for social unrest) averaged per multi-litter cage (N = 15 per treatment) treatment and observation day (1, 3, 6, 8, and 10 days after grouping). Higher activity scores represent a higher amount of movement and thus a higher rate of social unrest in the cage.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have also shown positive effects of consumable cage enrichment, such as the introduction of gnawing blocks, which reduced nest box inspections by does and decreased nervousness in fattening rabbits ( 34 , 35 ). In the study of Birolo et al ( 36 ), growing rabbits housed in groups exhibited active and positive responses toward new environments and objects when their cages were provided with compressed hay blocks.…”
Section: Discussionmentioning
confidence: 99%